Phonological, Morphological and Semantic Transformations of the Aymara Surnames: Quispe, Mamani, Colque, Choque And Condori - Arocutipa Saira, Milusca T. (2021)
At some point in their lives, people wonder about the meaning of their first and last names. However, few get to know it, since many of these come from an original language; which, over time, lost their meaning and originality, due to contact between languages and cultures.Therefore, this article analyzes from the anthroponymic approach the transformations that have occurred at the phonological, semantic or morphological level in Aymara surnames; For this, the written documentation method is used, since it uses] research carried out on Aymara surnames. In this sense, the article concludes that the surnames that underwent phonological, morphological and semantic transformations, due to the substitution of stop phonemes for simple phonemes, the substitution of Aymara phonemes for Spanish phonemes and the addition of phonemes, which caused the loss of its meaning and originality.